Opening New Opportunities For Aeronautic, Naval And Train Large Components Realization With Hybrid And Twin Manufacturing - Matthieu Rauch; Jean-Yves Hascoet (Journal of Machine Engineering)
Additive Manufacturing proposes innovative directions for high value components and has benefitted from large research efforts for almost all existing industrial sectors. This paper introduces some opportunities and the associated challenges attached to Additive Manufacturing, to produce large metallic components for naval aeronautics and train industries. Two innovative approaches are discussed. Hybrid manufacturing consists in integrating AM together with other processes with the objective to benefit from the interests of each process while avoiding its drawbacks. Finding the optimal manufacturing work plan can be challenging. Twin manufacturing uses models and multiphysics simulation to create a digital clone of the process implementation within its environment. Various configurations and choices can be tested before being selected. The digital twin can also be fed by monitoring data captured during the process. The paper is illustrated with several proof-of-concept parts.